User Experience Evaluation of the Internal Quality Assurance Information System (E-AMI) using the User Experience Questionnaire Plus (UEQ+) - Ni Putu Anik Mentayani; I Made Candiasa; I Made Gede Sunarya (Universitas Islam Indragiri, 2026)
This study evaluates the user experience (UX) of the E-AMI system at Primakara University, an academic quality assurance system managed by the Quality Assurance Institution (LPM). A sequential explanatory mixed-method design was employed, combining quantitative measurement using the User Experience Questionnaire Plus (UEQ+) across 15 scales with qualitative data collected through observations and semi-structured interviews. A total of 41 respondents participated, consisting of administrators, auditors, and auditees actively involved in the Internal Quality Audit (AMI) process. UEQ+ scores range from -3 (very negative) to +3 (very positive), with scores above 1.0 generally classified as good. The quantitative results yielded an average KPI score of 2.10, indicating good user experience quality, with the highest scores recorded in usefulness (M = 2.51), efficiency (M = 2.26), and perspicuity (M = 2.38). These findings were corroborated by qualitative data confirming the system's effectiveness in supporting core AMI processes. However, both quantitative and qualitative findings converged on several persistent UX weaknesses: Importance-Performance Analysis (IPA) identified visual aesthetics (M = 1.41), novelty (M = 1.90), attractiveness (M = 1.91), stimulation (M = 1.95), and value (M = 1.98) as priority improvement dimensions, consistent with qualitative findings of unintuitive navigation, insufficient system feedback, interface inconsistencies, and incomplete feature support. It is concluded that while the E-AMI system performs well in functional dimensions, further development in visual, experiential, and feature dimensions is required to achieve optimal UX quality, with future improvements recommended to adopt a user-centered design approach.